Structure of quench condensed nH2-N2 binary alloys: isotope effect: Quantum Crystals - Galtsov, N.N.; Prokhvatilov, A.I.; Strzhemechny, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Structure of quench condensed nH2–N2 alloys was investigated by powder x-ray diffraction over a wide range of temperatures, compositions, and rates of deposition. The structure of the deposits is shown to depend on the condensation regime. Under mild regime, no solid nitrogen reflections from hydrogen-rich deposits were observed. When the temperature is increased to the hydrogen triple point, nitrogen lines appear at substantially larger angles compared to pure N2, which suggests presence of dissolved hydrogen. The quantum nature of this hydrogen is suppressed in the nitrogen matrix. The samples grown in mild regime exhibit the highest apparent solubility (up to 25%) of hydrogen in solid N2. When H2 is substituted by D2, the isotope effect consists in a wider range of mono-phase states based on the nitrogen cubic lattice, which can accommodate up to 70% of deuterium, if grown under mild regime.